Cardiac troponin i activity compared with other cardiac markers in the dry period, early, and peak lactation in dairy cattle - Ali HAJIMOHAMMADI; Mojtaba BARMAKI; Daryoush BABAZADEH; Saeed NAZIFI; Seyed Amin RAZAVI; Mojtaba DANESHI (Kafkas Universitesi Veteriner Fakültesi Dergisi)
The current study aimed to evaluate the effects of parturition and different stages of milk production on Cardiac Troponin I activity (CTnI) and other cardiac markers. A total of 42 healthy dairy cattle with an average body weight of 520±17 kg and an average parity of 2.4±0.7 were randomly selected from a commercial dairy farm. Through a clinical examination and ECG recording conducted by a veterinarian, blood samples were collected from all cattle"s coccygeal vein one month before parturition (dry period), one week after parturition (early lactation), and 10 weeks after parturition (peak of the lactation). Dairy cows in the experimental group were observed closely before and during parturition and in the postpartum period. Biochemical parameters, including Cardiac Troponin I activity (CTnI), Creatine kinase (CK), Aspartate aminotransferase (AST), and Lactate dehydrogenase (LDH) were analyzed at three-time intervals. Regarding time intervals, there were no significant differences among the cattle in terms of CTnI, CK, LDH, AST, parturition, and different stages of milk production. It was found that the effect of late-stage gestation and different lactation periods on cardiac biomarkers in dairy cows was not significant.